ANALISA PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN MRA (STUDI KASUS PADA GALANGAN KAPAL DI SIDOARJO) - Widya Indraswari; R.A Norromadani Yuniati; Ristanti Akseptori (Proceeding Maritime Business Management Conference, 2022)
This company is a company in the shipping industry located in Sidoarjo, East Java. The purpose of this study was to determine the influence of compensation and job satisfaction on employee performance which is moderated by job satisfaction. This type of research is a quantitative research with a causal approach. The sample in this study amounted to 34 employees with purposive sampling technique. Data collection techniques used were interviews and questionnaires (questionnaires). The statistical test technique used was Moderated Regression Analysis (MRA). The results showed that compensation had no partial and significant effect on performance with the results of the t statistical test calculation of 0.063 and job satisfaction did not moderate compensation on performance with the results of MRA test calculation of 0.686. Therefore, company should manage their human resources in oder to optimize performance.